2016
DOI: 10.1007/s10803-016-2951-x
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Self-Injurious Behaviors in Children with Autism Spectrum Disorder: Findings from Two Large National Samples

Abstract: In this study, we explored potential associations among self-injurious behaviors (SIB) and a diverse group of protective and risk factors in children with autism spectrum disorder from two databases: Autism and Developmental Disabilities Monitoring (ADDM) Network and the Autism Speaks-Autism Treatment Network (AS-ATN). The presence of SIB was determined from children’s records in ADDM and a parent questionnaire in AS-ATN. We used multiple imputation to account for missing data and a nonlinear mixed model with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
57
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(64 citation statements)
references
References 72 publications
6
57
1
Order By: Relevance
“…; Soke et al . ). In addition, individuals with SIB showed more impairment in SRS‐2 total scores than those without SIB, suggesting that individuals with SIB also display increased challenges in their social functioning.…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…; Soke et al . ). In addition, individuals with SIB showed more impairment in SRS‐2 total scores than those without SIB, suggesting that individuals with SIB also display increased challenges in their social functioning.…”
Section: Discussionmentioning
confidence: 97%
“…These findings are somewhat inconsistent with previous work, which has largely found that younger children (Soke et al . ), individuals with higher ASD severity, and higher levels of RRBs and hyperactivity/impulsivity are more likely to engage in SIB (Baghdadli et al . ; Oliver et al .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations